Ab initio Infrared Spectra and Inversion Barriers of Dibenzo [a,c]cycloocta-5,8-diones - KASSAEE, M.Z.; ARSHADI, S.; BEKHRADNIA, A.R.; ASADI, M. (Asian Journal of Chemistry, 2010)
Ab initio calculations are carried out for stereo-specific inversions of 6XX´-7YY´-dibenzo[a,c]cyclooctadiene-5,8- dione, 1: X=X´=Y=Y´=H; 2: X=X´=Y=Y´=CH3; 3: X=Y= H, X´=Y´=CH3; 4cis: Y´=H, X´=Y=CH3; 4trans : X´=CH3, Y´=Y=H; 5cis: X=Y´=H, X´=Y= i-pr and 5trans: X=X´= i-pr, Y´=Y=H. Inversion energy barriers of 1–5, to their corresponding conformers 1'–5', are determined via ab initio calculations. These are preformed at HF/6-31G* and MP2/6-31+G* levels of theory, using Gaussian 98 system of programs. The order of energy barriers/(kcal/mol) found for the inversions is: 3⇌3' (34.00) > 2⇌2' (28.05) > 5cis⇌5'cis (27.21) > 5trans⇌5'trans (24.75) > 4cis⇌4'cis (22.35) > 4trans⇌ 4'trans (21.62) > 1⇌1' (19.47). Enantiomeric conformers 4cis and 4´cis have the same energy. Similarly, 5cis and 5´cis, which are mirror images, have the same energy. Diastereomeric conformers 4trans and 4´trans are at different energies. So are 5trans and 5´trans. Important factor that cause to observing two absorbance for each of cis and an absorbance for each of 4trans and 4´trans; 5trans and 5´trans is relative position of carbonyl group and closer benzene ring.